How Descriptive Norms and Peer Attitudes Shape Interethnic Dating Among Adolescents in Dutch Schools - Eva Jaspers; Pascale I. van Zantvliet; Jan-Willem Simons (Social Inclusion)
This study examines the role of school‐based environmental factors in shaping interethnic dating patterns among adolescents in the Netherlands. Given that adolescence is a formative period for social behaviour, early interethnic dating experiences may foster openness to interethnic marriage later in life. We focus on how general peer approval of the outgroupfrom both the ingroup and outgroup perspectivesand descriptive norms (i.e., the prevalence of interethnic relationships) influence adolescents’ partner choices. Using longitudinal data from the Dutch part of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU), we test whether ingroup attitudes influence interethnic dating via personal preferences for interethnic dating, and whether descriptive norms and outgroup attitudes moderate the relationship between personal preferences and dating. Results support the hypothesis that more positive ingroup attitudes are indirectly associated with an increased likelihood of interethnic dating via personal preferences. Descriptive norms furthermore moderate the effect of personal preferences, strengthening the relationship under supportive normative conditions. In contrast, we find no evidence that outgroup attitudes towards the ingroup play a moderating role. Ethnic minority adolescents and older students are more likely to date someone from an ethnic outgroup, while students with more highly educated parents and Christian students (vs. non‐religious peers) are less likely to do so. Future research should explore additional sources of normative influence, such as (social) media and adolescent clubs, to better understand the broader forces shaping interethnic relationships.